This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
= ( 3 i + 4 i ) ( 4 i − 8 i ) = 7 i ⋅ − 4 i = − 2 8 i 2 = 2 8
Simple standard approach.
Multiply i and 3 Multiply i and 1 The i just gets copied along. The answer is i 3 i evaluates to 3i Multiply i and 4 Multiply i and 1 The i just gets copied along. The answer is i 4 i evaluates to 4i 3 i+4 i evaluates to 7i Multiply i and 4 Multiply i and 1 The i just gets copied along. The answer is i 4 i evaluates to 4i Multiply i and 8 Multiply i and 1 The i just gets copied along. The answer is i 8 i evaluates to 8i 4 i-8 i evaluates to -4i Multiply 7i and -4i Multiply the i and i Multiply i and i Combine the i and i by adding the exponents, and keeping the i, to get The answer is (3 i+4 i) (4 i-8*i) evaluates to The final answer (almost!) is Now, let's simplify the i's to get our final answer: The i2 in can be simplified to -1. So, the becomes 28 . The final answer is 28
Erm... Can u write that in equation form??? Pls?
3 i 1 i
3i ( When multiplying i 1 =i) 4 I 1*i
4i ( When multiplying i 1 =i) (3 i+4 i) = 7i 8 I 1*i
8i ( When multiplying i 1 =i) (4 i-8 i) = (-4i) From the condition, (3 i+4 i)(4 i-8 i) = (7i)(-4i) [i i=i2 ] =(-28i2 ) =(-28)(-1) [i=√-1] [i2 =-1] =28 The answer is 28.
Problem Loading...
Note Loading...
Set Loading...
i is common in both the parenthesis and you are done. i 2 = − 1